2008
DOI: 10.1080/03079450802043742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protection elicited by direct and indirect exposure to live attenuated infectious laryngotracheitis virus vaccines against a recent challenge strain from the United States

Abstract: In a recent study , some field strains of infectious laryngotracheitis viruses (ILTV) were characterized as genotypically different (group VI) from ILT vaccine strains. The objective of this study was to evaluate the protection elicited by one chicken embryo origin (CEO) and one tissue culture origin (TCO) vaccine against a field isolate from group VI after direct and indirect exposure to ILTV live attenuated vaccines. In phase 1 of the experiment, non-vaccinated chickens were placed into contact with the eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
2
17
2
19
Order By: Relevance
“…Birds that were vaccinated via DW had detectable ILTV for at least up to 28 days. These findings are in contrast with a previous report (Rodriguez-Avila et al, 2007), where ILTV DNA was not detected in the trachea of vaccinated chickens after the first week post vaccination but then was detected again on days 10 and 14 post vaccination. This difference may be due to different sensitivities of the qPCR protocols used in each study, or to variations in replication patterns of the different ILTV vaccine strains.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Birds that were vaccinated via DW had detectable ILTV for at least up to 28 days. These findings are in contrast with a previous report (Rodriguez-Avila et al, 2007), where ILTV DNA was not detected in the trachea of vaccinated chickens after the first week post vaccination but then was detected again on days 10 and 14 post vaccination. This difference may be due to different sensitivities of the qPCR protocols used in each study, or to variations in replication patterns of the different ILTV vaccine strains.…”
Section: Discussioncontrasting
confidence: 57%
“…A previous report has revealed that, in contrast to vaccination, experimental exposure to ILTV vaccine strains by contact does not necessarily protect birds against challenge with wild-type ILTV (Rodriguez-Avila et al, 2008). Also a field study has postulated that, due to uneven distribution of the vaccine in poultry sheds, DW vaccination does not provide uniform protection against challenge in a flock (Fulton et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the Bastos strain 8 years after the initiation of vaccination in this region demonstrates that the attenuated vaccines were not able to eliminate this strain from the vaccinated region and that field ILTV strains can circulate without the presence of classical clinical signs. It has been suggested that CEO and field viruses can persist on vaccinated farms with chickens that are long-lived and/or of multiple ages, and the absence of clinical signs of ILT could be the outcome of the enhanced biosecurity measures applied and mass vaccination (Graham et al 2000;Dufour-Zavala 2008;Guy and García 2008;Rodriguez-Avila et al 2008;Chin et al 2009). There was a low rate of vaccine virus detection in the Bastos region, despite the massive vaccination program in this region.…”
Section: Discussionmentioning
confidence: 97%
“…External factors, including conditions at hatching and during rearing, are likely to be responsible for the different initial weights of 3-week-old birds in the different studies. Weight gain has previously been used to measure the pathogenicity of ILTV and to assess protection against challenge Rodriguez-Avila et al, 2008;Oldoni et al, 2009). A recent study, however, found that viral load and clinical signs after challenge were more reliable measures of protection than body weight gain (Johnson et al, 2010).…”
Section: Discussionmentioning
confidence: 98%